Single-Level Station Complex Structure for Application of Through Driving Construction Method - A. О. Kolikov; G. P. Pastushkov (Наука и техника)
Metro Service has a huge impact on the development of urban transport infrastructure. The need to increase the efficiency of passenger transportation is caused by the rapid growth in passenger turnover as well as an increase in the distance from the outskirts of the city to the center. In connection with the need to develop a metro service network in Minsk city, which is confirmed by research in the area of passenger traffic in the main areas of the city, the CSM Bessac tunnel boring machine was purchased, which allows significantly to increase the speed of  tunnel driving. The use of a mechanized tunnel boring machine in the traditional concept of the metro network construction, in which driving of tunnels is carried out after construction of stations, does not allow to use a shield with maximum economic efficiency due to the small extent of tunnels.  There is also a need to build assembly-shield chambers and carry out works on disassembling and  assembling  the shield. The application of the new concept developed by Yu. S. Frolov and called “through driving” is actual in the conditions of the use of a mechanized tunnel boring machine. Its essence lies in the continuous driving of tunnels on the line section under construction and the consecutive construction of each station complex as the tunnel boring machine passes through it. To implement the concept of “through driving”, it is relevant to use a semi-closed construction method, in which the floor structure is constructed in an open way, and the other elements are closed. The available solutions of the metro stations constructed while using a semi-closed method of work have been analyzed in the paper. A detailed analysis has been carried out with due account of the adaptation to the construction conditions in Minsk, and the development of structural elements and assemblies of the platform area of the station, which is a two-cantilever vault with a developed transom part, resting on pile-columns of a circular cross section. Forces from the open ring of flexible tunnels lining are supported by a cantilever part of an arch and a bottom plate. The paper considers a design of a metro station, its main elements, their purpose and specificity of work, as well as optimization issues and the results of the design feasibility study.